Pengaruh Kompetensi Bidang Akuntansi dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Desa Di Kecamatan Ketapang Kabupaten Sampang - Ulfatus Zuhroh (SUSTAINABLE JURNAL AKUNTANSI, 2021)
ABSTRACT Â This research was conducted to determine the effect of competence in the field of accounting on the quality of village financial reports in Ketapang sub-district, Sampang district; The Influence of the Internal Control System on the Quality of Village Financial Reports in Ketapang District, Sampang Regency; The Influence of Competence in Accounting and the Effect of Internal Control Systems on the Quality of Village Financial Reports in Ketapang District, Sampang Regency. This research includes survey research. The population in this study were village officials in 14 villages in Ketapang District, Sampang Regency are 56 people. The data collection technique used is a questionnaire. The analysis prerequisite test includes validity and reliability tests as well as classical assumption tests which include normality, heteroscedasticity and multicollinearity tests. The data analysis technique used is multiple regression analysis. The results of the study show that the Competence of the Accounting Sector has an effect on the Quality of Village Financial Reports in Ketapang District, Sampang Regency is 0,059 or 5,9%; The Internal Control System affects the Quality of Village Financial Reports in Ketapang District, Sampang Regency is 0,082 or Â 8,2%; Competence in the field of accounting and internal control systems simultaneously affect the quality of village financial reports in Ketapang District, Sampang Regency is 14,2%, while the remaining 85,8% is influenced by other variables outside of this research.Keywords: Accounting Competence, Internal Control System, Quality of Village Financial Reports.ABSTRAK Penelitian ini dilakukan untuk mengetahui Pengaruh Kompetensi Bidang Akuntansi terhadap Kualitas Laporan Keuangan Desa di Kecamatan Ketapang Kabupaten Sampang; Pengaruh Sistem Pengendalian Intern terhadap Kualitas Laporan Keeanga Desa di Kecamatan Ketapang Kabupaten Sampang; Pengaruh Kompetensi Bidang Akuntansi dan Pengaruh Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan Desa di Kecamatan Ketapang Kabupaten Sampang. Penelitian ini termasuk penelitian survei. Penelitian ini merupakan penelitian populatif. Populasi pada penelitian ini adalah perangkat desa di 14 desa yang ada di Kecamatan Ketapang Kabupaten Sampang sebanyak 56 orang. Teknik pengumpulan data yang digunakan adalah kuesioner. Uji prasyarat analisis meliputi uji validitas dan reliabilitas serta uji asumsi klasik yang meliputi uji Normalitas, Heteroskedastisitas dan Multikolinieritas. Teknik analisis data yang digunakan adalah analisis regresi berganda. Hasil penelitian menunjukkan Kompetensi Bidang Akuntansi berpengaruh terhadap Kualitas Laporan Keuangan Desa di Kecamatan Ketapang Kabupaten Sampang sebesar 0,059 atau 5,9%; Sistem Pengendalian Intern berpengaruh terhadap Kualitas Laporan Keuangan Desa di Kecamatan Ketapang Kabupaten Sampang sebesar 0,082 atau 8,2%; Kompetensi Bidang Akuntansi dan Sistem Pengendalian Intern secara simultan berpengaruh terhadap Kualitas Laporan Keuangan desa di Kecamatan Ketapang Kabupaten Sampang sebesar 14,2%,sedangkan sisanya 85,8% dipengaruhi oleh variabel lain di luar penelitian ini.Kata Kunci: Kompetensi Bidang Akuntansi, Sistem Pengendalian Intern, Kualitas Laporan Keuangan Desa.